Engage employees and transform social and economic performance - Grayson, David; McLaren, Melody (Cranfield University, 2011)
Forward thinking companies embrace intrapreneurs and employee social interaction to develop sustainability programmes driven from the top down and bottom up.
Keywords: MT=CRS